2011
DOI: 10.3892/ijmm.2011.795
|View full text |Cite
|
Sign up to set email alerts
|

Beyond neurological disease: New targets for edaravone (Review)

Abstract: Abstract. Free radicals play major roles in the pathogenesis of tissue damage in many diseases and clinical conditions, and the removal of free radicals may offer a treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 85 publications
(124 reference statements)
1
10
0
Order By: Relevance
“…Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one) is a potent free-radical and protein carbonyl scavenger and inhibitor of lipid peroxidation [57-58]. Protein carbonylation and carbonyl stress via aldehydes occur in COPD and hence edaravone has the potential to protect the lungs against the effects of these oxidative products [59-60].…”
Section: Lipid Peroxidation and Protein Carbonylation Inhibitors/blocmentioning
confidence: 99%
“…Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one) is a potent free-radical and protein carbonyl scavenger and inhibitor of lipid peroxidation [57-58]. Protein carbonylation and carbonyl stress via aldehydes occur in COPD and hence edaravone has the potential to protect the lungs against the effects of these oxidative products [59-60].…”
Section: Lipid Peroxidation and Protein Carbonylation Inhibitors/blocmentioning
confidence: 99%
“…Edaravone has been widely used in patients with AIS since April 2001 in Japan, because many clinical and experimental studies have demonstrated neurovascular protective effects [1115]. Furthermore, edaravone has anti-apoptotic, anti-necrotic, and anti-inflammatory cytokine effects, as well as scavenging free radicals in cardiovascular diseases and stroke, showing protective effects in the heart, vessel, and brain in experimental studies [1619]. Moreover, edaravone has preventive effects on myocardial injury following ischemia and reperfusion (I/R) in patients with acute myocardial infarction (AMI) [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, only 1-2% of patients can receive thrombolytic therapy mainly due to the short time window (no more than 3–6 h after stroke) and the possible complication such as hemorrhagic transformation (HT) and brain edema [2]. Although edaravone, a free radical scavenger [3, 4], has been used in Asian countries for many years, it is still not approved by the United States and Europe because of its side effects in liver and kidney and only a small clinical trial found that edaravone might improve outcomes [57]. Thus, additional effective new drugs are urgently needed.…”
Section: Introductionmentioning
confidence: 99%